COMMUNITY VIEWS ON PULMONARY TUBERCULOSIS: A STUDY OF KNOWLEDGE AND BEHAVIOR - HUSSAIN , J; HAMEED , A; SHAKOOR , A; ASHRAF , M; AYUB , A (Biological and Clinical Sciences Research Journal, 2024)
Inadequate understanding of tuberculosis (TB) may impact patients' inclination to seek medical care and perpetuate the spread of the disease among the community. This study aimed to evaluate the understanding and perspective of individuals who appear to be in good health regarding pulmonary tuberculosis (PTB)). Objectives: To explore the knowledge and behavior of the population about pulmonary TB. Methods: The study was conducted using a cross-sectional design. A survey using a questionnaire was done on 165 randomly selected healthy individuals after obtaining verbal agreement from all participants. SPSS 23 was used to analyze the data. The chi-square test was applied to obtain the required results. Results: The findings indicated that the average age of the participants was 45.33 ± 1.49 years, ranging from 19 to 67 years. Out of the total, 42 individuals (25.46%) were females, while 123 individuals (74.54%) were males. Out of the respondents, 70 (42.42%) acknowledged that they were aware of the bacterial cause of TB. Eighty percent of individuals are aware that tuberculosis can be treated. The most prevalent symptom of tuberculosis (TB) was the presence of blood in the sputum, accounting for 101 cases (61.21%). In health institutions, contemporary pharmaceuticals were the favored treatment option, chosen in 70 cases (42.42%). Conclusion: The results suggest that communities possessed basic knowledge about the disease. However, it is essential to provide health education to change their traditional beliefs and views of the condition into factual knowledge.